Cellular non-specific interstitial pneumonia masquerading as congestive heart failure. (3rd September 2013) - Saraya, Takeshi; Takata, Saori; Fujiwara, Masachika; Takei, Hidefumi
Abstract : A 66-year-old woman with a history of myocardial infarction 2 months prior presented to our respiratory department with several days of dry cough and night sweats. Chest X-ray and thoracic CT showed ground glass opacities or consolidation spreading from the hilar area to the peripheral area, suggesting central redistribution. Although neither rales nor abnormal heart sounds were noted, she was tentatively diagnosed with congestive heart failure based on those radiological findings. However, radiographic lung lesions and her symptoms were refractory to intensive diuretic treatment. Thereafter, video-assisted thoracoscopic surgery was performed, resulting in a diagnosis of cellular non-specific interstitial pneumonia (c-NSIP). After initiating treatment with prednisolone, her symptoms and the radiological findings resolved. In patients with NSIP, a radiological central distribution could rarely occur, especially in cases of c-NSIP. No rales were detected because of its paucity of fibrous components in the lung.